Relaxor behaviour of K0.5Bi0.5NbO3- BiScO3ceramics - Chatchai Kruea-In (2018)
Dielectric properties of (1 - x)K0.5Bi0.5TiO3- xBiScO3ceramics have been studied for compositions x < 0.5. Single-phase solid solutions occurred for compositions x < 0.25. A frequency-dependent dielectric relaxation was observed, consistent with relaxor behaviour. This gave rise to a relatively stable dielectric permittivity at high temperatures, for example,r2880 ± 3, between temperatures of 500 and 700 K (1 kHz) for composition x = 0.15. This consistency in relative permittivity occurs at higher temperatures than for other lead-free dielectrics. Parameters from Vogel-Fulcher analysis are compared to other relaxors. © 2012 American Institute of Physics.